TUHAN, MANUSIA DAN ALAM DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Tita Rostitawati (LP2M IAIN Sultan Amai Gorontalo, 2018)
Object study of philosophy of Islamic education can be divided into two categories: macro and micro. The study of God, man and nature are the object of a macro philosophy of Islamic education. If there is a nature-nature, then there is first nature (al-Haqq al-Awwal), the first is the nature of God or called Causa Prima, and ends or returns to God anyway. Man is the manager of God's creation, while human nature as a means of doing, all three have an associated role between one and the other. The human ability to manage natural and translate the revelation of God is the manifestation and harmonious manner. Instead the human capacity to manage natural but was unable to translate the revelation of God is considered as a form of perversion, because humans ignore creation. On the other hand the human ability to translate the revelation of God but not able to translate nature is considered as a form of denial of pasilitas given to man by God. So, we need a complate understanding between the three. The universe is the medium of education as well as the means by which the human family to carry out the educational process. In this universe man can not live and the